Analisis Urgensi Skybridge dalam Mendukung Pergerakan dan Interaksi Antar Ruang di Kawasan Transit Solo Solo Balapan dan Tirtonadi - Nabiel, Muhammad; Pujantiyo, Bambang S.; Permana, Raden Chrisna Trie H. (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
In Surakarta City, there is a skybridge connecting Solo Balapan Station and Tirtonadi Bus Station, both of these transit stations plays a significant role in improving the efficiency and connectivity of the intermodal transportation system. However, the use of this facility is still low by an average daily user of only 100 people compared to transit station’s daily average of +18.000 users. This study aims to determine the urgency of the skybridge in supporting inter-regional interaction in the transit area. The analysis method used is the analysis of movement patterns and the gravity model to measure the value of inter-regional interaction. The results of the analysis show that the value of skybridge interaction with other areas is relatively low and there is no internal movement by transit area users. This indicates that the potential movement that may occur from the area around the transit area (skybridge) is low. based on the results of the analysis, the skybridge has no urgency in supporting the movement around the Solo Balapan transit area and Tirtonadi Terminal.